2005
DOI: 10.1002/gps.1381
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy of donepezil in Parkinson's disease with Dementia and Dementia with Lewy bodies

Abstract: Donepezil produced similar improvements in cognition and behaviour in DLB and PDD. This supports the hypothesis that the two disorders are closely related clinically and neurobiologically. Larger scale, placebo controlled clinical trials are needed to provide an evidence base to guide the clinical use of cholinesterase inhibitors in Lewy body disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 36 publications
(33 reference statements)
5
62
0
Order By: Relevance
“…[51] Arguing against a role for the cholinergic system in depression is the lack of robust evidence for a significant impact of cholinesterase inhibitors on mood in PD (e.g. [52]), although, to date, there have been no randomized trials with depression as a primary outcome. A second possible mechanism underpinning an association between axial symptoms and depression is white matter change.…”
Section: Discussionmentioning
confidence: 99%
“…[51] Arguing against a role for the cholinergic system in depression is the lack of robust evidence for a significant impact of cholinesterase inhibitors on mood in PD (e.g. [52]), although, to date, there have been no randomized trials with depression as a primary outcome. A second possible mechanism underpinning an association between axial symptoms and depression is white matter change.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, it is suggested that cholinesterase inhibitors (ChEIs) may be effective for treating DLB. In fact, usefulness of ChEIs such as galantamine, rivastigmine, and donepezil in the treatment of DLB symptoms has been reported in several open-label studies [5,6,7,8,9] and two randomized controlled trials [10,11]. Their usefulness has also been reported in several clinical trials of Parkinson's disease dementia, which is considered to fall into same category as DLB [12,13].…”
Section: Introductionmentioning
confidence: 88%
“…The cholinergic loss and a choline acetyltransferase activity deficit with preserved postsynaptic cortical muscarinic and nicotinic receptors [3,4,5] rationalizes the use of cholinesterase inhibitors (ChEIs) in DLB. The favorable potential of ChEls such as galantamine, rivastigmine, and donepezil has been demonstrated in previous studies [6,7,8,9,10,11]. The phase 2 and 3 trials of donepezil in patients with DLB have added to the accumulating evidence of the efficacy and safety of donepezil in terms of cognitive, behavioral, and global function in DLB, even for long durations, without increasing the risk of clinically significant safety events [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%